Implementasi Penguatan Karakter Pada Anak-Anak Desa Huta Tinggi - silaban, bajonggaa; Franjimson Naiborhu; Anggun Oktavia Naibaho; Destriani C. br Nainggolan; Gresia Ledy Sinaga; Erlin Juniati Manullang; Herman Christian F. Aruan (JCSE: Journal of Community Service and Empowerment, 2023)
Strengthening character education in today’s times is very important to instill in children at an early age. Given the number of crimes that occur, it shows the moral crisis that is plague among the community. The value of character in man cannot grow, but rather develop through the process of living and learning from the environment. The value of such character that will become the identity of a person when acting in society. Therefore the value of character in man must be taught and familiarized from an early age. The purpose of this devotion is to improve the strengthening of children’s character in Huta Tinggi village Pangururan district Samosir district through devotion program to the community (PkM). Through the demonstration method, volunteers (lecturers and students) implemented improved character education in children in non-formal classes. The event also aims to apply 5 characters in children, which consists of religious, homeland love, creativity, critical, and social. The program is designed with a variety of activities that can attract children and packed with semi-formal delivery so that it creates a pleasant atmosphere of the community in Huta High village. By improving the character of children will give hope to the next generation of moral nation to create welfare in the midst of society.